Implementation Of Information And Communication Technology In Improving Intellectual Competence Of Reserved Components Through Integrated Training And Monitoring System Of Reserve Components (SPMT Komcad) In Inactive Periods. (Qualitative Analytical Descriptive Study on MAN 1 and MAN 2 Tasikmalaya Regency) - Luxni Maulana; Yusnaldi; Bayu Asih; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
Reserve Component as a national resource that is prepared to be deployed through mobilization to enlarge and strengthen the strength and capability of the main components, TNI and POLRI. The existence of an active period and an inactive period of Komcad on the other hand becomes a question whether Komcad can maintain its intellectual competence during an inactive period. This study aims to determine the use of information and communication technology in increasing the intellectual competence of reserve components through the Reserved Components Integrated Training and Monitoring System (SPMT Komcad) during inactivity. The method used in this research is a quantitative approach. The data collection technique in this research is using literature study, the authors develop a system with the waterfall model, namely sequentially starting from the analysis, design, coding, testing and support stages. The results of this study are the increase in intellectual competence of reserve components can be done through an integrated training and monitoring system for Reserve Components (SPMT Komcad). SPMT Komcad can be a solution to the concerns of spare components in maintaining their competence in inactive periods.